2016
DOI: 10.1002/ptr.5614
|View full text |Cite
|
Sign up to set email alerts
|

Erectogenic and Aphrodisiac Property ofMoringa oleifera: Involvement of Soluble Epoxide Hydrolase Enzyme

Abstract: Soluble epoxide hydrolase (sEH) inhibitors have been reported to improve penile erection; therefore, sEH could be useful for management of erectile dysfunction. Methanolic and aqueous extracts of 30 Indian medicinal plants were screened for their sEH inhibition potential. Fifteen extracts showed >50% inhibition when screened at 50 µg/mL in sEH inhibition assay. Methanolic extract of Moringa oleifera Lam. (Moringaceae) seeds (MEMO) was most potent with IC50 1.7 ± 0.1 µg/mL and was selected for in vitro studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…This result is in agreement with the report of Pasco and Leopold (2012) where high sugar diet was reported to induce the observable features of type‐2 diabetes in flies. These effects were mitigated by the varieties of moringa leaf in the diet, this might be due to the ability of moringa to inhibit soluble epoxide hydrolase and inhibition of soluble epoxide hydrolase has been reported to ameliorate diabetes and its complications (Goswami et al., 2016; Nathani, Rema, Bruce, & Sumanta, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This result is in agreement with the report of Pasco and Leopold (2012) where high sugar diet was reported to induce the observable features of type‐2 diabetes in flies. These effects were mitigated by the varieties of moringa leaf in the diet, this might be due to the ability of moringa to inhibit soluble epoxide hydrolase and inhibition of soluble epoxide hydrolase has been reported to ameliorate diabetes and its complications (Goswami et al., 2016; Nathani, Rema, Bruce, & Sumanta, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Another study also demonstrated that oral administration of aqueous extract of MO leaves (100, 200 and 500 mg/kg)to male rats for 21 days enhanced male sexual behaviour and libido activity (Zade et al., 2013), an indication of the function of testosterone in the male reproductive system. Also, administration of methanolic extract of MO seeds (45 and 90 mg kg ‐1 day ‐1 ) for 21 days to normal and diabetic male rats enhanced sexual activities (Goswami et al., 2016). Oral administration of ethanol extract of MO leaves (100, 200 and 400 mg/kg) for 30 days significantly increased LH, FSH and testosterone levels (Dafaalla et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is a medicinal plant with several pharmacological activities which include antidiabetic, antihypertensive, antioxidant, and hypolipidemic activities (Chumark et al ; Verma, Vijayakumar, Mathela, & Rao, ). Extract of drumstick seed and leaves were also reported to exhibit aphrodisiac properties via suppression of soluble epoxide hydrolase (Goswami et al, ) oxidative stress, monoamine oxidase, and phosphodiesterase activities as well as increase in serum testosterone levels (Prabsattroo et al, ). Previous reports have shown that a Drumstick leaf extract inhibited arginase and ACE activities while Nutmeg and Drumstick seeds have been reported to possess aphrodisiac properties (Muchtaridi et al, ; Oboh, Ademiluyi, et al, ; Prabsattroo et al, ).…”
Section: Introductionmentioning
confidence: 99%